Advances and challenges in immunotherapy in head and neck cancer - Aboaid, Hazem; Khalid, Taimur; Hussain, Abbas; Myat, Yin Mon; Nanda, Rishi Kumar; Srinivasmurthy, Ramaditya; Nguyen, Kevin; Jones, Daniel Thomas; Bigcas, Jo–Lawrence; Thein, Kyaw Zin (Frontiers in Immunology, 2025)
Head and neck squamous cell carcinoma (HNSCC) remains a challenging malignancy with suboptimal survival outcomes despite advances in surgery, radiotherapy, and chemotherapy. Immunotherapy, particularly immune checkpoint inhibitors (ICIs) targeting programmed cell death protein 1 (PD-1)/programmed cell death ligand 1 (PD-L1), has transformed treatment paradigms, yet its full potential in HNSCC is still being explored. This review evaluates the current landscape of immunotherapy in both locally advanced (LA) and recurrent/metastatic (R/M) HNSCC, discussing key clinical trials, emerging biomarkers, and novel therapeutic strategies. For LA HNSCC, phase III trials such as KEYNOTE-412 and JAVELIN Head and Neck 100 failed to demonstrate survival benefits with ICI-chemoradiotherapy combinations in unselected populations, though post hoc analyses suggest efficacy in PD-L1–positive tumors. Recent studies, including KEYNOTE-689 and NIVOPOSTOP GORTEC 2018-01, indicate potential benefits of perioperative ICIs in resectable disease. In R/M HNSCC, ICIs have redefined the standard of care. KEYNOTE-040 and CheckMate 141 led to Food and Drug Administration (FDA) approvals of pembrolizumab and nivolumab, while KEYNOTE-048 established pembrolizumab monotherapy for PD-L1 combined positive score (CPS) ≥1 and pembrolizumab plus chemotherapy as first-line treatment. However, dual checkpoint blockade trials (KESTREL, CheckMate 651) have yielded mixed results, highlighting the complexity of immune resistance. Beyond ICIs, emerging strategies include oncolytic virotherapy, chimeric antigen receptor-T cell therapy (CAR-T), and cancer vaccines, with promising preclinical and early-phase clinical results. Biomarkers such as PD-L1 expression, tumor mutational burden (TMB), and Human Papillomavirus (HPV) status play a critical role in treatment selection, but further validation is needed. Despite advancements, challenges persist, including heterogeneous response rates, immune-related toxicities, and optimal integration of immunotherapy in multimodal treatment regimens. Future research should focus on refining biomarker-driven treatment algorithms, developing rational immunotherapy combinations, and leveraging tumor microenvironment modifications to enhance therapeutic efficacy.